1999
DOI: 10.1211/0022357991772222
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by the Bioflavonoid Ternatin of Aflatoxin B1-induced Lipid Peroxidation in Rat Liver

Abstract: Aflatoxin B1, a metabolite of Aspergillus flavus is a potent hepatotoxic and hepatocarcinogenic mycotoxin. Lipid peroxidation and oxidative DNA damage are the principal manifestations of aflatoxin B1-induced toxicity which could be mitigated by antioxidants. Many plant constituents, e.g. flavonoids, lignans and spice principles (capsaicin, curcumin, eugenol, etc.) have been reported to prevent liver damage associated with lipid peroxidation. In this study we investigated ternatin, a tetramethoxyflavone isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 18 publications
(19 reference statements)
3
39
0
Order By: Relevance
“…24,25 Previous studies, using different animal species, indicated that AF induced changes in oxidative stress markers. 6,[26][27][28][29] This study was conducted to assess the effect of AF on oxidative stress signs in rat liver, heart and kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Previous studies, using different animal species, indicated that AF induced changes in oxidative stress markers. 6,[26][27][28][29] This study was conducted to assess the effect of AF on oxidative stress signs in rat liver, heart and kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant enzymes can be induced or inhibited in the blood cells exposed to different toxicants and these enzymes play a main role in the defence of mammalian blood (Prasad et al 2006). Souza et al (1999) reported that the oxidative stress is the principle manifestation of AFB 1 -induced toxicity which could be mitigated by antioxidants. Our previous study (Turkez et al 2007) and the current study well establish that BA alone does not lead to the induction of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) In a previous study, we established the gastroprotective effects of both CPA and tanabolin against indomethacin and ethanolinduced gastric lesions, validating the traditional use of E. viscosa.…”
mentioning
confidence: 70%
“…14) Pharmacological investigations identified the anti-inflammatory, hepatoprotective, antidiarrhoeal and gastroprotective properties of ternatin. 15,16) In a previous study, we established the gastroprotective effects of both CPA and tanabolin against indomethacin and ethanolinduced gastric lesions, validating the traditional use of E. viscosa. 17) However, the gastroprotective mechanisms were not elucidated.…”
mentioning
confidence: 70%